Manajemen Bencana Gempa Besar dan Tsunami Jepang Timur dalam Ehon - Jun Arya Wangsa, I Gusti Ngurah; Damayanti, Silvia; Andry Anita Dewi, Andry Anita Dewi (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2025)
This study, titled "Disaster Management of the Great East Japan Earthquake and Tsunami in Picture Books," aims to explore how disaster management and its impacts during the 2011 earthquake and tsunami are represented in picture books (ehon). The research uses a literature study to gather data from ehon and a descriptive analysis to interpret it, presented narratively. It draws on Wellek and Warren's literary sociology, Danesi’s semiotics (2010), and the Japanese Cabinet Office’s Disaster Management Report (2021). The study finds that Japanese disaster management includes three phases: (1) mitigation (pre-disaster) with education and preparedness, (2) response (during disaster) with emergency actions, and (3) recovery (post-disaster) with rehabilitation and reconstruction. These are depicted in the ehon’s narratives and illustrations, though not all books cover every phase. Positive impacts include successful evacuations, survival post-disaster, and restoration of life, while negative impacts include family separation and school relocations.